The Digital Era in Pharmaceutical Chemistry: Transforming Drug Design with Computational Methods - Valdiviezo, Jesus (2023)
Drug design has significantly benefited from advancements in computational chemistry and neural networks. In this article, we explore the pivotal role played by computational chemistry techniques such as Density Functional Theory (DFT), Molecular Docking, and Molecular Dynamics (MD) in understanding and optimizing atomic and molecular-level interactions. Furthermore, we examine how the integration of neural networks has enhanced precision and efficiency in drug design. We present specific examples of research projects showcasing the synergy between these methods and highlighting substantial advances in the quest for effective medical solutions. Additionally, we discuss challenges and key considerations for continuing to progress in this multidisciplinary field.